Effect of Phenformin on the Response of Plasma Intestinal Glucagon-like Immunoreactivity (GLI) to Oral Glucose in Gastrectomized Subjects - Shima, K; Sawazaki, N; Morishita, S; Tarui, S; Nishikawa, M (Experimental Biology and Medicine, 1975)
The effect of phenformin (DBI) on the plasma intestinal glucagon-like immunoreactivity (GLI) and pancreatic glucagon (IRG) responses to oral and intravenous glucose loads were studied in 26 gastrectomized subjects, using a cross-reacting and an IRG-specific anti-serum. The drug produced no significant changes in fasting GLI and IRG levels. Thirty minutes after oral glucose alone, the total GLI level rose to a peak of 1.55 +/- 0.17 ng/ml in the untreated subjects and to a maximum level of 1.67 +/- 0.18 ng/ml in the DBI-pretreated subjects. However, the mean GLI levels obtained 120 and 180 min after oral glucose were significantly higher after treatment with DBI. The blood sugar and IRI responses to oral glucose were lowered significantly by DBI pretreatment. DBI did not alter the glucose, IRI, IRG and GLI response to intravenous glucose. These results suggest that the release of intestinal GLI is not related to the intestinal absorption of glucose.